Optimalisasi Potensi Pertumbuhan Ekonomi Masyarakat Lokal melalui Rekonstruksi Pariwisata Syariah Pulau Santen Banyuwangi Jawa Timur - Siti Masrohatin; Rini Puji Astuti (Journal on Education, 2023)
Optimizing the utilization of local potential is one of the next steps in community self-help that utilizes local potential and resources. This potential includes all existing potential such as natural resources, human resources, social resources. one form of optimizing the utilization of local potential in empowering the community's economy is through the utilization of the potential of human resources. Shariah Beach is a new concept of halal tourism and has become a promotional event for Banyuwangi Regency. The formulation of the problem that will be put forward is: How is the reconstruction of tourism on Santen Banyuwangi Island, which used to be free, now has a sharia concept? How does the district government or tourism manager involve the local community, either directly or indirectly, who contribute to the local community on Santen Banyuwangi Island?.This type of research includes the type of qualitative research, descriptive research methods. Data analysis techniques: data collection, data reduction, data presentation and conclusion. Research results 1)Reconstruction of tourism which used to have a free concept that seemed dirty, dirty and had negative ideals has now turned into a sharia beach so that it has the benefit of increasing income and empowering youth so that no one is unemployed after being recruited to become members of the Pokdarwis on Santen Island 2) District government or administrator tourism involves the local community both directly and indirectly which contributes to empowering the local community on Banyuwangi Santen Island, the management of Santen Island with residents is still not optimal. While contributions in the economic sector increase people's income, in the education sector increase teaching and learning activities, in the socio-cultural field it favors the culture of local people who use Javanese and Madurese.